Podoplanin expression in cutaneous head and neck squamous cell carcinoma—prognostic value and clinicopathologic implications1. Issue 4 (6th August 2012) - Kreppel, Matthias; Krakowezki, Anton; Kreppel, Barbara; Drebber, Uta; Wedemeyer, Inga; Mauch, Cornelia; Zöller, Joachim E.; Scheer, Martin
Abstract Background Although most patients are cured by local treatment from cutaneous head and neck squamous cell carcinoma (cHNSCC), a significant number of patients develops metastases to the regional lymph nodes. Recent studies suggest an influence of podoplanin expression on regional lymph node metastases in other head and neck squamous cell carcinoma. The aim of our study was to assess the impact of podoplanin expression on regional lymph node metastasis, locoregional recurrence, and prognosis. Methods In this retrospective study, podoplanin expression was examined immunohistochemically in 63 treatment‐naive patients with cHNSCC. We analyzed associations of podoplanin expression and clinicopathologic variables. Furthermore, we investigated the effects on overall survival (OS) and locoregional control in univariate and multivariate analysis. Results In 40 patients (63.5%), podoplanin was expressed in the tumor cells. The χ2‐test revealed that podoplanin expression was associated with the number of tumorous lymph nodes (P < 0.001). The OS was significantly influenced by podoplanin expression (P < 0.001). None of the patients with high levels of podoplanin expression survived, whereas the 5‐year OS for patients with podoplanin‐negative tumors was 91.3%. Conclusions We concluded that podoplanin is frequently expressed in cHNSCC and might serve as predictor for regional lymph node metastases, locoregional recurrence, and clinical outcome. J. Surg. Oncol. 2013;107:376–383. © 2012 Wiley Periodicals, Inc.